Dual antiplatelet therapy with clopidogrel and aspirin increases mortality in 4T1 metastatic breast cancer-bearing mice by inducing vascular mimicry in primary tumour - Smeda, Marta; Kieronska, Anna; Proniewski, Bartosz; Jasztal, Agnieszka; Selmi, Anna; Wandzel, Krystyna; Zakrzewska, Agnieszka; Wojcik, Tomasz; Przyborowski, Kamil; Derszniak, Katarzyna; Stojak, Marta; Kaczor, Dawid; et al. (Oncotarget, 2018)
Platelet inhibition has been considered an effective strategy for combating cancer metastasis and compromising disease malignancy although recent clinical data provided evidence that long-term platelet inhibition might increase incidence of cancer deaths in initially cancer-free patients. In the present study we demonstrated that dual anti-platelet therapy based on aspirin and clopidogrel (ASA+Cl), a routine regiment in cardiovascular patients, when given to cancer-bearing mice injected orthotopically with 4T1 breast cancer cells, promoted progression of the disease and reduced mice survival in association with induction of vascular mimicry (VM) in primary tumour. In contrast, treatment with ASA+Cl or platelet depletion did reduce pulmonary metastasis in mice, if 4T1 cells were injected intravenously. In conclusion, distinct platelet-dependent mechanisms inhibited by ASA+Cl treatment promoted cancer malignancy and VM in the presence of primary tumour and afforded protection against pulmonary metastasis in the absence of primary tumour. In view of our data, long-term inhibition of platelet function by dual anti-platelet therapy (ASA+Cl) might pose a hazard when applied to a patient with undiagnosed and untreated malignant cancer prone to undergo VM.